The Development of First‐Episode Direct Self‐Injurious Behavior and Association with Difficulties in Emotional Regulation in Adolescence. Issue 5 (3rd September 2018) - Palmer, Colin; Connor, Charlotte; Channa, Sunita; Lavis, Anna; Leung, Newman; Parsons, Nick; Birchwood, Max
Abstract : Objective: Self‐harm remains a serious public health concern; however, identifying adolescents at risk is challenging. While self‐harm has been linked with difficulties in emotional regulation postinjury, comparatively little is known about how such difficulties may impact on the future development of self‐harm behavior. Methods: A total of 318 pupils aged 14–15 years completed measures on history of direct self‐injurious behavior (D‐SIB), emotional regulation, depression, and anxiety at two time points across a six‐month period. Results: Of 13% (42) of participants reported their first episode of D‐SIB over the six‐month period and reported increased difficulties with emotional regulation prior to initial D‐SIB. Regression analyses found significant associations for emotional regulation and specifically lack of emotional clarity prior to first episode of D‐SIB. Lack of emotional awareness and difficulties with impulse control was significantly associated in those with ongoing D‐SIB. Conclusions: Prior to first episode of D‐SIB, young people may experience difficulty regulating emotions, a difficulty which appears less pronounced following their engagement with D‐SIB. Our findings implicate difficulties in the early evaluation and understanding of emotions which may later impair attempts at emotion modulation and increase risk of D‐SIB. Such findings might help inform early identification of adolescents at risk of initial D‐SIB.